Sociodemographic and behavioral risk factors for cervical cancer, its awareness and preventive practices among reproductive age group women in a slum area of Kolkata - Sinjita Dutta; Shalini Pattanayak; Afifa Ahamed; Mausumi Basu (IMC Journal of Medical Science)
Background and objectives: Women residing in Indian slums remain at risk of developing cervical cancer because of lack of awareness and effective screening programs. This study aimed at identifying sociodemographic and behavioral risk factors for cervical cancer, its awareness, and preventive practices among reproductive age-group women in a slum of Kolkata.